Medication, rehabilitation and health care consumption in adults with cerebral palsy: a population based study. (July 2017) - Pons, Christelle; Brochard, Sylvain; Gallien, Philippe; Nicolas, Benoit; Duruflé, Aurélie; Roquet, Marion; Rémy-Néris, Olivier; Garlantezec, Ronan
Objective: To evaluate medication, rehabilitation and healthcare consumption in adults with CP as a function of Gross Motor Function Classification System (GMFCS) level. Design: Questionnaire-based cross-sectional study. Setting: Brittany, a French county. Subjects: Adults with cerebral palsy. Interventions: Questionnaires relating to drugs, orthotic devices, mobility aids, rehabilitation and medical input were sent to 435 members of a unique regional French network dedicated to adults with cerebral palsy. The questionnaire was completed by the participant or a helper if necessary. Results: Of the 282 responders, 7.8% had a GMFCS level of I, 14.2% II, 17.7% III, 29.1% IV and 31.2% V. Participants consumed a large amount of healthcare. Almost three-quarters took orally administered drugs, of which antispastic and antiepileptic drugs were among the most frequent. Nearly all patients had at least one type of rehabilitation, 87.2% had physiotherapy, 78% used at least one mobility aid and 69.5% used at least one orthotic device. The frequency of numerous inputs increased with GMFCS level. Specificities were found for each GMFCS level, e.g. participants with GMFCS level IV and V had a high level of medical input and a greater use of trunk-supporting devices, antireflux and laxative. Profiles could be established based on GMFCS levels. Conclusions: Adults with cerebral palsy use a large amount of drugs, mobility aids, orthotic devices, rehabilitation and medical input. Healthcare is targeted at cerebral palsy-related issues. GMFCS is a determinant of healthcare consumption and thus a useful tool for clinical practice to target care appropriately.